Dampak Media Sosial Terhadap Pemasaran Informasi Di Perpustakaan Universitas Lancang Kuning - Indah Chintami Andiraa; Leady Yurmeli Br Barus; Nining Sudiar (CV. ITTC INDONESIA, 2023)
In this 4.0 era, the majority of people are already using social media. Not only individuals, social media is also made for organizations and institutions. Each institution has a library with its own advantages. In this day and age, most university libraries are already using a digital system, although the manual system is still there. UNILAK libraries use social media as a library marketing tool. This strategy is used for various purposes, namely to promote the printed collection as well as the collection of e-books and e-journals. The use of social media is very effective to inform users about new collections. Not only informing about collections, social media can also be used to inform services and activities in the library. Another benefit of using social media in this library is that information sharing becomes more effective and reaches a wider range of users. Social media for libraries can also encourage librarians to innovate and increase creativity in creating new forms of service that have not existed before in libraries. To provide information about the services available in the library, a librarian can not only inform in written form, but can also do so by informing it through moving images equipped with sound (audio visual).